Modern Approach To The Using Of Informations Technologies For Organization Educational Process. - A. Bychkov; Y. Chernii (Kherson State University, 2009)
The system of creation of the distance learning course are proposed. with the controlled from distance access for independent preparation; this computer system does not require knowledges of information technologies from teachers.